Epididymal Leiomyosarcoma: One Case Report - Tazi, Mohammed Fadl (Hindawi Publishing Corporation, 2012)
Epididymal leiomyosarcoma is very uncommon. Only 16 cases have been reported in the literature. There has never been a reported case of a patient with an African origin with this tumor. We report the medical history of a 70-year-old man who presented an enormous mass located in his epididymis. A tricut biopsy was performed which allowed histological confirmation of epididymal leiomyosarcoma after which the patient underwent excision of the mass. The patient died after the first round of chemotherapy.